The Application of Functional Nanomaterials-Based Electrochemical Biosensors in Detecting Cancer Biomarkers: A Review - Meiyin Liu; Yuchen Song; Meiru Liu; Dongmei Deng; Wenjiao Zhang; Ting Wang; Liqiang Luo (Molecules, 2025)
Cancer remains a leading cause of morbidity and mortality worldwide. The timely and accurate detection of potential early cancer biomarkers is essential for early cancer diagnosis. In recent years, electrochemical biosensors have garnered significant attention due to their portability, cost-effectiveness, and ease of use. In addition, given their exceptional physicochemical properties, functional nanomaterials have found extensive applications in the field of electrochemical biosensing. This review provides an overview of the basic principles and types of electrochemical biosensors, the classification and properties of functional nanomaterials, and the application of functional nanomaterial-based electrochemical biosensors in the detection of cancer biomarkers. Finally, the prospects and remaining challenges of functional nanomaterial-based electrochemical biosensors in cancer diagnosis are discussed.